Design and analysis of scaled composite UHBR fan blade for wind tunnel tests - Noordman, B.A.T.; Vankan, W.J. (ICAS, 2024)
Future aircraft have to comply with strict environmental targets like reductions in CO2, NOx and noise emissions. Ultra-High Bypass Ratio (UHBR) turbofan engines with large fan diameters are promising in terms of reduction of fuel consumption and emissions. To investigate the challenging integration of such an UHBR engine in the airframe, an experimental scaled turbofan model is being developed to perform a wind tunnel test campaign. For the fan stage of this turbofan model composite fan blades are designed that shall resist the high centrifugal and aerodynamic loads for different flight conditions. For the design and analyses of the composite fan blade, a detailed finite element method (FEM) modelling approach is developed taking into account accurately the 3D blade geometry including blade foot, composite material properties, fibre directions and composite layup of the blade design. This detailed FEM modelling approach is validated with test results of geometrically simplified composite test elements. Blade hot-to-cold analyses are applied to the Aerodynamic Design Point (ADP-S1) flight condition to retrieve the blades’ cold shape that will be manufactured. With the cold shape of the blade design the hot shapes are calculated for different flight conditions and blade twist angles and blade tip radial displacements are checked. Campbell diagrams for the blade design are generated for the first 3 eigenmodes to assess the blade’s vibrational behaviour under operational conditions. The first three blade eigenfrequencies at zero rotational speed were compared with test blade tap test results, which agreed quite well.